2020
DOI: 10.3390/w12082169
|View full text |Cite
|
Sign up to set email alerts
|

Combining Hydrogeochemical Characterization and a Hyperspectral Reflectance Tool for Assessing Quality and Suitability of Two Groundwater Resources for Irrigation in Egypt

Abstract: Hyperspectral reflectance sensing provides a rapid and cost-effective technique for assessing the suitability of groundwater for irrigation by monitoring real-time changes in its quality at a large scale. In this study, we assessed the quality of 15 groundwater samples from El Fayoum depression in the Western Desert (WD) and 25 groundwater samples from the Central Nile Delta (CND) in Egypt using a traditional approach of the physiochemical parameters, irrigation water quality indicators (IWQIs), and hydrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…The concentrations of trace elements occurred in the following sequence: [66]. The low concentrations of trace elements indicated that there were no significant effects on the irrigation water suitability [48]. For example, El-Bana [75], El-Bana et al [76] and El Bouraie et al [7] studied the temporal variation of Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn in Nile River water in the northern Nile Delta and the effects of these elements on the water quality.…”
Section: Physicochemical Parameters and Water Faciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of trace elements occurred in the following sequence: [66]. The low concentrations of trace elements indicated that there were no significant effects on the irrigation water suitability [48]. For example, El-Bana [75], El-Bana et al [76] and El Bouraie et al [7] studied the temporal variation of Al, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn in Nile River water in the northern Nile Delta and the effects of these elements on the water quality.…”
Section: Physicochemical Parameters and Water Faciesmentioning
confidence: 99%
“…Over the past decade, several research initiatives have been aimed at creating and enhancing water quality prediction models [45][46][47]. Recently, machine learning and data-driven results have shown promising results in the development of precise water quality estimation models [48,49]. Therefore, multivariable statistical regression methods, including the PCR, SVMR and SMLR, were tested as alternative approaches for predicting WQIs for irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…The NSRIs-2b was calculated as a ratio spectral index according to Gad et al [55] as shown in Table 1 and as follows:…”
Section: Selection Of Newly Constructed and Commonly Used Spectral Reflectance Indicesmentioning
confidence: 99%
“…Although SRIs are a simple tool and several indices have been efficiently used in estimating WQIs, they are hindered by their use of just a few bands and are impacted by environmental conditions, timeliness, and regional specificity [55,81,86]. Furthermore, using several wavebands sensitive to water quality parameters through SRIs combined with PLSR models could enhance the performance of the models to predict the WQIs.…”
Section: Performance Of Plsr Models To Predict Water Quality Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation